Genetics of resistance to leaf rust in wheat - ANUJ KUMAR and RAMCHARAN, P. BAHADUR, DINESH SINGH, (Indian Phytopathology, 2002)
Genetic analysis for leaf rust resistance in five Indian wheat cultivars of diverse origin viz., HD 2329, HD 2402, PBW 343, UP 262 and WH 542 was carried out with 3 pathotypes of leaf rust (Puccinia recondita f. sf). tritici) i.e. 77-2 (109R31-1), 104-2 (21R55) and 106 (OR9). Segregation of seedlings in F2 BC1 and BC2 for resistance to above pathotypes suggested the presence of one dominant gene for resistance in HD 2402, two dominant independent genes each in WH 542, UP 262 and PBW 343 and one dominant and one recessive gene in HD 2329. Analysis of BC 1 and BC 2 with above pathotypes confirmed the above results. Reciprocal crosses of above cultivars also supported these findings. Monogenic segregation in crosses involving HD 2402 with WH 542, UP 262 and PBW 343; WH 542 with HD 2329, UP 262 with HD 2329, and PBW 343 with HD 2329, to pathotype 77-2 (109R31-1) and absence of susceptible segregants in F2 in most intercrosses of resistant parents to pathotype106 (OR9) indicated the presence of at least one common gene in these wheats. Based on seedling resistance test (SRT) of above wheat with 14 pathotypes, Lr14a in HD 2402, Lr26 in WH 542 and PBW 343 and Lr10, Lr13 in HD 2329 were identified.